Kingdom of the Netherlands : Aruba; Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2008)
The statistical data on indicators of tourism activity, gross domestic product (GDP) and components, real GDP, contributions to real GDP growth, changes in consumer price index and legal minimum wages in Aruba are detailed. Summary of trends in public finance, tax revenue, operational budget of the social insurance bank, government debt, balance of payments summary, non-oil balance of payments summary, monetary survey, monetary developments, and contributions to broad money growth have also been included in the given statistical data.